1999
DOI: 10.1007/s002560050477
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular gouty tophi of the knee: CT and MR imaging in 12 patients

Abstract: Presenting clinical manifestations of gout may relate to intra-articular tophaceous deposits. Such deposits present as masses on MR images with low to intermediate signal intensity on both T1- and T2-weighted images and a characteristic enhancement pattern following intravenous Gd administration. These features relate primarily to internal calcifications, which are most evident on CT images. MR evaluation (including Gd administration) supplemented, in some cases, with CT scanning allows accurate diagnosis of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 7 publications
6
45
2
Order By: Relevance
“…This is not unusual as the appearance of tophaceous gout on an MRI is usually nonspecific. [6,9,10] Therefore, an open biopsy was deemed necessary to come to a definitive diagnosis. We chose this over needle biopsy to ensure that we got an adequate tissue for sampling.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unusual as the appearance of tophaceous gout on an MRI is usually nonspecific. [6,9,10] Therefore, an open biopsy was deemed necessary to come to a definitive diagnosis. We chose this over needle biopsy to ensure that we got an adequate tissue for sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Since the MRI findings of tophaceous gout are non-specific, tophi mimic a tumor or an infection on MR images. Intra-articular tophi have been detected by intermediate to low signal intensity on T1 weighted MR images and various intensities on T2 weighted MR images 4,5) . In the present case, a diffuse mass in the pos- terior compartment of the knee was detected as low intensity on T1 weighted MR images and high intensity on T2 weighted MR images.…”
Section: Discussionmentioning
confidence: 99%
“…These features relate primarily to internal calcifications, which are most evident on CT scans. Magnetic resonance imaging scan (including Gd administration) supplemented, in some cases, with CT scan allows accurate diagnosis of intraarticular tophaceous deposits [9]. Monosodium urate (MSU) deposits within a tophus can be clearly defined with CT scan.…”
Section: Ozkan Et Al 595mentioning
confidence: 99%
“…Photomicrograph of another section had been stained by de Galantha's method for demonstration of monosodium urate crystals ( Figure 2). subcutaneous nodules, knee, acromioclavicular joint and axial skeleton [3][4][5][6][7][8][9][10][11][12][13][14]. A recent study suggested that the frequency of axial involvement may be as high as 14% in patients with clinical or crystal-proven gout [15].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation